Two new species of Oocyclus Sharp from China with a revised key to the genus for mainland Southeast Asia (Coleoptera: Hydrophilidae) - Short, Andrew Edward Z.; Jia, Feng-Long (Zootaxa, 2011)
Two new species of water scavenger beetles, Oocyclus fikaceki Short & Jia sp. n. and O. dinghu Short & Jia sp. n. are described from Guangdong, Fujian, and Jiangxi Provinces in southeastern China. A revised key to the species of the genus in Indochina and surrounding mainland regions is presented.